2020
DOI: 10.1002/iub.2327
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA LINC01207 promotes prostate cancer progression by downregulating microRNA‐1972 and upregulating LIM and SH3 protein 1

Abstract: Prostate cancer is a heritable and clinically heterogeneous cancer. Both long non‐coding RNAs (lncRNAs) and microRNAs (miRs) have been implicated in the pathogenesis and development of prostate cancer. Analysis of microarray data indicated that the lncRNA LINC01207 was differentially expressed in prostate cancer. In silico analysis predicted the interaction between LINC01207 and miR‐1972 as well as the interaction between miR‐1972 and the mRNAs LIM and SH3 protein 1 (LASP1). Thus, we explored the role of LINC0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Several miRNA molecules and other proteins such as kallikreins have been proposed as PC biomarkers ( 6 ). In addition, LINC01207 was previously reported to be highly expressed in prostate cancer, as it could downregulate miR-1972 and upregulate LIM and SH3 protein 1 to promote PC progression ( 35 ). In the present study, LINC01207 seems to act as an oncogenic gene through modulating miR-1182/AKT3 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNA molecules and other proteins such as kallikreins have been proposed as PC biomarkers ( 6 ). In addition, LINC01207 was previously reported to be highly expressed in prostate cancer, as it could downregulate miR-1972 and upregulate LIM and SH3 protein 1 to promote PC progression ( 35 ). In the present study, LINC01207 seems to act as an oncogenic gene through modulating miR-1182/AKT3 axis.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA LINC01207, located in the 4q32 genomic locus with three exons and two introns, has been reported to be upregulated in multiple types of cancer and associated with the prognosis of patients with poor survival (205)(206)(207)(208)(209). Recent studies have demonstrated that LINC01207 performs as an oncogenic lncRNA to promote cell growth, migration, invasion, and enhance apoptosis, as well as maintain stemness via ceRNA regulatory mechanism.…”
Section: Linc01207/mir-143-5p/agr2mentioning
confidence: 99%
“…The accumulated evidence demonstrates that cytoplasmic lncRNA acts as a ceRNA and decoy for certain miRNAs in human cancers. [30][31][32] Accordingly, a ceRNA model was utilized in the mechanistic studies. Using the miRDB, 36 miRNAs ( Figure 3D) were predicted as potential binding partners of LINC00519.…”
Section: Dovepressmentioning
confidence: 99%